Acceptability and study of shelf life of gluten free cereal bar with popped and extruded sorghum based on a consumer acceptability (Caderno de Ciências Agrárias, 2018)
Cereal bars have been an excellent vehicle for delivering functional ingredients to food market. Researches has showed that sorghum is a great source of phenolic compounds. Besides, it is a gluten free cereal, therefore a potential ingredient to celiac diets. Thus, a cereal bar with popped sorghum, sorghum extrudates, cashew fiber and dehydrated banana was formulated. Sensory acceptability of this product was determined by two panels: one panel composed of celiac individuals and another by non-celiac subjects. The product shelf life was estimated by the acceptability limit methodology. After remained stored for 120 days under 25 °C, the shelf life was estimated at 163 ± 52 days. The sensorial study has not found significant differences in relation to overall acceptability between celiac and non-celiac individuals. This study suggest that sorghum co-products could be used successfully as a food ingredient to develop new formulations of the gluten free cereal bars. ResumoBarras de cereais têm sido uma excelente alternativa para oferecer ingredientes funcionais ao mercado de alimentos. Pesquisas têm mostrado que o sorgo é uma grande fonte de compostos fenólicos. Além disso, é um cereal sem glúten, portanto, um ingrediente potencial para dietas celíacas. Assim, uma barra de cereal com pipoca de sorgo, sorgo extrusado, fibra de caju e banana desidratada foi formulada. A aceitabilidade sensorial deste produto foi determinada por dois painéis: um painel composto por indivíduos celíacos e outro por indivíduos não celíacos. O prazo de validade do produto foi estimado utilizando-se a metodologia do limite de aceitabilidade. Após permanecer armazenado por 120 dias a 25 ° C, o tempo de vida útil foi estimado em 163 ± 52 dias. O estudo sensorial não encontrou diferença significativa em relação à aceitabilidade geral entre indivíduos celíacos e não celíacos. Este estudo sugere que coprodutos de sorgo podem ser usados com sucesso como ingredientes alimentares para desenvolver novas formulações de barras de cereais sem glúten.